Method of treatment of post-necrotic cysts of pancreas - S. V. Morozov; V. L. Poluektov; V. T. Dolgikh (Бюллетень сибирской медицины, 2006)
Aimed at obliteration, percutaneous punctures under control of ultrasound examination with inserting of 2—4 mg of cyclophosphan in 10—20 ml of 0,9% of NACl solution with exposure of 15 minutes were performed in 18 patients having postnecrotic cysts of pancreas. Mean size of the cysts was 12,6 mm. Obliteration of the cysts occurred in 10—14 days. Together with cytostatic action, e obliteration effect of cyclophosphan was due to its influence on exudation and proliferation processes unlike spirit and iodine. The method is more effective in non-formed cysts.